CHARACTERISTICS OF HYBRID SYSTEMS FOR ELECTRICITY GENERATION AND APPLICATIONS IN WIND-PHOTOVOLTAIC SYSTEMS - Siqueira, J. A. C.; GABRIEL FILHO, L. R. A.; Caneppele, F. L.; Seraphim, O. J. (Revista Brasileira de Engenharia de Biossistemas, 2014)
A hybrid system uses jointly more than one source of energy for the generation of electricity in which one source complements the eventual failure of the other. The system may be a combination of one or more forms of generation, employing wind power, solar photovoltaic systems, diesel, water, or others, even though energy storage system is not mandatory. Solar and wind power system may be underscored among the energy sources used by hybrid systems since they feature renewable characteristics. The success of their implementation depends directly on the reliability of the operation to the power supply and to the cost of the energy produced. Current study introduces several systems´ characteristics for the generation of electricity. Regarding system design, it is important to analyze costs and usages of the system coupled to electrical system factors, such as charge loss and battery life. A photovoltaic-wind system was built at the Faculty of Agronomic Sciences of Botucatu (UNESP) to disseminate and specify the components of a hybrid system for the generation of electric power. Several research works were performed at the Center for Alternative and Renewable Energies of the Laboratory for Rural Energy of the Agricultural Engineering Department in Botucatu SP Brazil